2017
DOI: 10.1523/jneurosci.1534-16.2017
|View full text |Cite
|
Sign up to set email alerts
|

Are There Multiple Kinds of Episodic Memory? An fMRI Investigation Comparing Autobiographical and Recognition Memory Tasks

Abstract: What brain regions underlie retrieval from episodic memory?The bulk of research addressing this question with fMRI has relied upon recognition memory for materials encoded within the laboratory. Another, less dominant tradition has used autobiographical methods, whereby people recall events from their lifetime, often after being cued with words or pictures. The current study addresses how the neural substrates of successful memory retrieval differed as a function of the targeted memory when the experimental pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
90
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(107 citation statements)
references
References 66 publications
13
90
1
Order By: Relevance
“…We hypothesized that the DMN would be an important component of differences between states, as it has been widely associated with autobiographical memory in previous studies (Buckner and Carroll, 2007; Chen, et al, 2017; Ino, et al, 2011; Philippi, et al, 2015). Within the retrieval-resting difference network, 22 DMN regions were found.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We hypothesized that the DMN would be an important component of differences between states, as it has been widely associated with autobiographical memory in previous studies (Buckner and Carroll, 2007; Chen, et al, 2017; Ino, et al, 2011; Philippi, et al, 2015). Within the retrieval-resting difference network, 22 DMN regions were found.…”
Section: Discussionmentioning
confidence: 99%
“…Regions with activity evoked by specific autobiographical memory retrieval demands include the hippocampal formation, medial prefrontal cortex (mPFC), posterior cingulate cortex (PCC), temporal poles, and temporo-parietal junction, forming a core autobiographical memory network (Buckner and Carroll, 2007; Chen, et al, 2017; Rabin, et al, 2009; St Jacques, et al, 2011; Svoboda, et al, 2006). This network of regions associated with autobiographical memory overlaps considerably with the default-mode network (DMN), which can be robustly measured using activity timeseries correlation analyses during resting-state fMRI scans, without any explicit task (Buckner, et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Face stimuli were taken from several publicly available databases: The Psychological Image Collection at Stirling’s 2D face set (http://pics.psych.stir.ac.uk/); the CNBC Tarrlab “Face Place” repository (wiki.cnbc.cmu.edu/Face_Place; Righi et al, 2012); the Park Aging Mind Laboratory Face Database (agingmind.utdallas.edu/facedb; Minear and Park, 2004); and Libor Spacek’s Facial Imaging Database (cmp.felk.cvut.cz/~spacelib/faces/). Scene stimuli were drawn from a larger set reported by Chen et al (2017). Lexical properties used to create the abstract and concrete word lists were sourced from the English Lexicon Project (Balota et al, 2007).…”
Section: Star Methodsmentioning
confidence: 99%
“…Thus, it is perhaps unsurprising that neuroimaging studies comparing the profile of brain activity during the retrieval of stimuli learned in a laboratory context to that associated with the retrieval of autobiographical memories (i.e., memories for one's own life events) typically find marked differences. For instance, autobiographical memory retrieval evokes much greater activation of default mode network regions implicated in introspective cognition and self‐referential processing—such as the medial prefrontal cortex (mPFC)—as well as medial temporal lobe (MTL) regions associated with recollection of visuospatial contextual details, such as the hippocampus and parahippocampal cortex . Indeed, a meta‐analysis of functional magnetic resonance imaging (fMRI) studies of episodic retrieval revealed only limited anatomical overlap in the neural correlates associated with the retrieval of laboratory‐encoded and autobiographical memories .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a meta‐analysis of functional magnetic resonance imaging (fMRI) studies of episodic retrieval revealed only limited anatomical overlap in the neural correlates associated with the retrieval of laboratory‐encoded and autobiographical memories . Moreover, performance on standard laboratory‐based memory tasks can be largely unrelated to one's autobiographical retrieval abilities, as demonstrated by individuals with either “highly superior autobiographical memory” or “severely deficient autobiographical memory.” Dissociations like these have led some to propose that retrieving autobiographical event knowledge is fundamentally different from other forms of episodic retrieval …”
Section: Introductionmentioning
confidence: 99%